Payment issues : the problems of Malaysian construction industry - Siti Nur Ashikin, Abu Bakar (2015)
ablishes buildings and infrastructure works required for social economic development which contribute to the overall economic growth. However, there remains a chronic problem of delayed and non-payment in the Malaysian construction industry affecting the entire delivery chain. However, there remains a chronic problem of delayed and non-payment in the Malaysian construction industry affecting the entire delivery chain. This research therefore set out to study the profiles of Malaysian court cases in relation to payment disputes in construction industry. The research is also to address the legal issues in relation to payment disputes based on the court cases also to investigate the problem, effects and legal issues disputed by contractor together to provide remedies of payment in construction industry. The result shows that payment has been an issue of major concern in the construction industry. As consequences, the payment due is postponed until the resolution of the dispute. The result shows that payment has been an issue of major concern in the construction industry. It really giving stress to contractor as it creates the cash flow problem. It also reflects the inadequacies and shortfalls of litigation process which take a long duration to determine the dispute. As consequences, the payment due is postponed until the resolution of the dispute. In summary, findings of this research may assist the relevant parties in addressing problems associated to late and non-payment in an effective and timely manner to create a win-win situation for all parties in the Malaysian construction industry